Molecular Simulation Assisted Discovery Learning to Improve Higher Order Thinking Skills in Chemical Equilibrium Concepts - Saputra, Andrian; Tania, Lisa (FKIP Universitas Lampung, 2021)
The purpose of this study is to describe the effectiveness of discovery learning assisted by molecular simulation to improve higher order thinking skills in chemical equilibrium materials. The method used in this study was a quasi-experimental with the matching only pretest-postest control group design. The population were all students of XI MIA MAN 1 Bandar Lampung in the academic year 2019/2020. The sample was XI MIPA 5 as an experimental class and XI MIPA 6 as a control class obtained by purposive sampling technique. The data analysis technique used was the t test. The results showed the n-gain average of students' high-level thinking skills in the molecular simulation assisted learning class were 0.78 with high criteria, whereas in the control class was 0.58 with medium criteria. The t-test results showed students n-gain in the experiment class was significantly higher than control class. It can be concluded that the discovery learning model assisted by molecular simulations was effective in improving students' higher order thinking skills.Keywords: chemical equilibrium, discovery learning models, higher order thinking skills, molecular simulation DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp315-323